Nouveau traitement de l'équation de Schrödinger modifiée pour le potentiel Cornell généralisé en l’espace phase non commutatif à deux dimensions dans les symétries de la mécanique quantique non commutatif - BENTOUMI, Mohamed Yakoub (UNIVERSITE MOHAMED BOUDIAF - M’SILA, 2020)
In this work, of master memory, in theoretical physics, (2019/2020), we have studied the Schrödinger equation with generalized Cornell potential in noncommutative two dimensional spaces and phases by applying the Bopp's shift method to first order in the noncommutative parameters ( , ), instead of using the star product method. The corrections of energy levels obtained by applying standard perturbation theory atoms with one electron, it has been observed that the obtained energy spectra was changed radically, and replaced by degenerate new states, depending on the discrete quantum atomic number m , these results produced from Zeeman effect.
Keywords: Star product, noncommutative space and phase, generalized Cornell potential. Paces number(s): 11.10.Nx, 32.30-r, 03.65-w.